A comparison of the use of mesh to native tissue in the management of vaginal vault prolapse. (January 2019) - Walter, Jens-Erik
Abstract: Vaginal vault prolapse afflicts millions of women and evokes significant psychosocial and pelvic floor dysfunction. The risk factors and modalities of conservative management are discussed in this study. There remains controversy in the optimal surgical management. This review serves to study the clinical conundrum of the decision-making process to utilize the mesh and the approach. In-depth evaluation of mesh-related postsurgical complications as compared to those associated with the native tissue is explored.